Taurine and protocatechuic acid attenuate Vincristine sulphate‑induced bone marrow, liver and intestinal injuries via anti‑oxidative, anti‑inflammatory and anti‑apoptotic activities (2024)
Chemotherapy with Vincristine (Vcr) is often compromised by undesirable gastrointestinal, myeloid and hepatic effects. In this study, we evaluated and compared the efficacy of taurine (Tau) and/or protocatechuic acid (Pca) in alleviating Vcr-induced hepatotoxicity, enterotoxicity and myelotoxicity in rats. In two cycles of five daily injections each, rats were exposed to Vcr (0.1 mg/kg, i.p.) alone or in combination with orally administered Tau (50 mg/kg) and/or Pca (50 mg/kg). Blood was collected for haematology and measurement of liver enzymes and inflammatory cytokines. Genotoxicity assay was performed on bone marrow, while the liver and intestines were subjected to biochemical assays, histopathology and immunohisto-chemical staining. Administration of Vcr triggered bone marrow suppression (anaemia, leucopenia, thrombocytopenia and increased frequency of micronucleated polychromatic erythrocytes, MnPCEs), increased serum transaminases (ALT, AST) and alkaline phosphatase (ALP) and altered hepatic and intestinal morphology. However, supplementation with Tau and/ or Pca alleviated most of the toxic effects of Vcr by reducing tissue levels of malondialdehyde (MDA), hydrogen peroxide (H2O2) and advanced oxidation protein products (AOPP), but stimulating glutathione S-transferase (GST) and glutathione per oxidase (GPx) activities. In addition, Tau and/or Pca enhanced anti-inflammatory (reduced serum TNFα) and anti-apoptotic mechanisms (reduced cytochrome c/Bax expression and increased Bcl-2 expression) in the ileum and liver. Overall, Tau or Pca protected the liver, ileum and bone marrow against Vcr-induced toxicities via antioxidant, anti-inflammatory and anti-apoptotic mechanisms. The data supports their individual use, rather than their combination, as adjuvant therapy in patients undergoing chemotherapeutic intervention.